2017
DOI: 10.18267/j.pep.601
|View full text |Cite
|
Sign up to set email alerts
|

GDP Forecasting by Czech Institutions: An Empirical Evaluation

Abstract: This paper evaluates the accuracy of real GDP growth forecasts published in the period 1995-2013 by two Czech institutions: the Ministry of Finance (MF) and the Czech National Bank (CNB). A two-stepped approach is adopted: first a battery of forecasting errors (MAE, RMSE, MASE) is calculated, complementary to evaluation papers already available. Then statistical analysis is carried out by comparing both MF and CNB forecasts with OECD, European Commission and consensus benchmarks (Kruskal-Wallis test), assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Forni, Gambetti, Lippi, & Sala (2017) found that noise shocks cause hump-shaped responses of GDP, consumption and investment, and explain a large part of their prediction error variance in business cycles. Sindelar (2017) showed that although some error patterns might indicate performance deficiencies, the validity of forecasts made by the Ministry of Finance in Czech and Czech National Bank does not differ much from the benchmark forecasting.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Forni, Gambetti, Lippi, & Sala (2017) found that noise shocks cause hump-shaped responses of GDP, consumption and investment, and explain a large part of their prediction error variance in business cycles. Sindelar (2017) showed that although some error patterns might indicate performance deficiencies, the validity of forecasts made by the Ministry of Finance in Czech and Czech National Bank does not differ much from the benchmark forecasting.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Nepoměrně bohatšími poznatky nicméně na druhé straně disponujeme v oblasti makroekonomických prognóz, které jsou základem fiskálního plánování. Ať už jde o evaluace vlastního Ministerstva financí (MF, 2013a), výstupů Výboru pro rozpočtové prognózy (VRP, 2022), případně dalších autorů (Šindelář, 2017;Antal, Hlaváček a Horvath, 2008;Novotný a Raková, 2011;aj.). Valná většina těchto studií indikuje konkurenceschopnost predikcí MF vůči dalším institucím (z hlediska jejich přesnosti) a nepřítomnost systémových chyb.…”
Section: úVodunclassified